Students’ Digital Literacy and Collaboration Abilities: An Analysis in Senior High School Students - Purnamasari, Lilis; Herlina, Kartini; Distrik, I Wayan; Andra, Doni (Universitas Islam Negeri Raden Intan Lampung, 2021)
This study aims to describe and analyze the level of digital literacy and collaboration skills of students. The research method used a quantitative descriptive survey with a research instrument in the form of a questionnaire. The study involved 10 physics teachers and 105 high school students in Lampung Province. The results showed that the digital literacy of students was in the sufficient category with the achievement percentage of 54.68%, while the collaborative abilities of students were in the poor category with the achievement percentage of 39.17%. Digital literacy has not been maximally achieved and the ability to collaborate in students is influenced by the lack of efforts of students to use the internet as a learning resource and the lack of student-centered learning.